PENGARUH PELATIHAN METODE SIMULASI TERHADAP PERILAKU KADER DALAM UPAYA PEMBERIAN ASI EKSKLUSIF - Jumiyati, Jumiyati (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Exclusive breastfeeding in Indonesia fluctuated and showed a tendency to decrease from the age of zero months to five months. The low coverage of exclusive breastfeeding is influenced by not maximal yet educational activities and fostering optimal breastfeeding support group. Breastfeeding support group can involve cadre by increasing knowledge, skills and training. The purpose of the study to determine the effect of training with simulation methods of behavior of cadres to effort exclusive breastfeeding. This research is a quasi experimental with a non- randomized control group pretest and post test. the ppopulation are 105 cadres with 60 samples . the Measurement of knowledge and skills done before and after the study. The results of the study can improve the of cadres knowledge about breastfeeding in the treatment group was higher than the control group with p = 0.001. so also skill cadre enhancement in the treatment group was higher than the control group with p = 0.001 (Training with simulation methods and administration modules can improve cadre behavior (knowledge and skills)